Audiogenic epileptic DBA/2 mice strain as a model of genetic reflex seizures and SUDEP - Bosco, Francesca; Guarnieri, Lorenza; Leo, Antonio; Tallarico, Martina; Gallelli, Luca; Rania, Vincenzo; Citraro, Rita; De Sarro, Giovambattista (Frontiers in Neurology, 2023)
Epilepsy is a chronic neurological disease due to an abnormal brain activity that results in repeated spontaneous seizures. Sudden unexpected death in epilepsy (SUDEP), is the leading cause of seizuresrelated premature death, particularly in drug-resistant epilepsy patients. The etiology of SUDEP is a structural injury to the brain, not fully understood, but it is frequently associated with poor controlled repeated generalized tonic-clonic seizures (GTCS) that cause cardio-respiratory and autonomic dysfunctions indicating a brainstem involvement.Both respiratory and cardiac abnormalities in SUDEP have been observed, but not much progress has been made in their prevention. Due to the complexity of SUDEP, experimental animal models has been used to investigate cardiac and/or respiratory dysregulation due to or associated with epileptic seizure that may contribute to death in humans. Numerous rodent models, especially mouse models, have been developed to better understand the epilepsy and SUDEP physiopathology. This review synthesizes the current knowledge about DBA/2 mice as a possible SUDEP model, because they show respiratory arrest (RA) and sudden death induced by audiogenic generalized seizures (AGSs). These mice also show respiratory/cardiac dysfunction, brainstem arousal system dysfunction, and alteration of the neurotransmitter systems, as those present in human SUDEP. In particular, alteration of serotonin (5-HT) and adenosine neurotransmission, seem contribute to the pathophysiological mechanisms of medication but also to seizure-related respiratory dysfunctions in this animal model. These neurotransmitter systems could be the relevant targets for medications development for chronic epilepsy and SUDEP prevention. We reviewed data on AGSs in DBA/2 mice and the relevance of this model of generalized tonic-clonic epilepsy to human SUDEP. Furthermore, the advantages of using this strain prone to AGSs for the identification of possible new therapeutic targets and new treatments have also been assessed.